Direito social ao lazer no Brasil : análise das contribuições da produção acadêmica difundida no campo da Educação Física : da Constituição Federal de 1988 aos dias atuais - Areias, Keni Tatiana Vazzoler (2011)
The research aimed to analyze in articles published in Congress, Seminars and Magazines about Public Policies of Leisure in Brazil from 1988 to 2009, the possible contributions that these productions brought to the consolidation of Leisure as a social law. We analyzed 83 articles, in wich we identified the concepts of social law, citizenship, social participation and leisure, to enable them to provide support for a rigorous analysis of the conception of man, world and society that are grounded in the theoretical field of leisure. We believe that studies of leisure are part of a larger context of intellectual production in Brazil and around the world, expressing social conflicts, influencing and being influenced by knowledge dissemination in a season. Considering the concepts of state, especially from the perspectives neoliberal and marxist, we identified important issues that relate these concepts to the design of state that they reinforce. We note the existence of a fault on the problematization of the concepts of citizenship and social law, treated as terms and almost self-explanatory without reference theory. Social participation is often confused with accountability of civil society, which weakens the state and gives power to the market. As for leisure, the discussion is decontextualized, which is not conducive to their connection with a project of social emancipation. Together, these articles do not offer an alternative to the neoliberal model of society and, therefore, does not reach the leisure legitimacy as a social law, restricting themselves to legality